The influence of E-HRM on modernizing the role of HRM context - A. Chamaru De Alwis; Berislav Andrlić; Marko Šostar (Economies, 2022)
Human Resource Management (HRM) practitioners must play multiple roles to achieve both functional and organizational objectives. In the current business environment, Electronic Human Resource Management (E-HRM) is a pervasive application of Information Technology (IT), and its global adoption is now widespread. This study's primary objective is to determine the effect of E-HRM implementation in Sri Lanka on the evolving HRM function. The study employed a qualitative methodology. On the basis of prior research, a study framework was formulated. After collecting the findings, the researcher analyzed the data using the study framework. To answer the research question and attain the research objectives, the researcher compared the theory to the findings during the analysis. The researcher determined that HRM was unfamiliar with E-HRM applications but was utilizing E-HR tools in their daily operations. According to the study, HRM places a greater emphasis on administrative tasks. The greatest benefit of implementing E-HRM practice is that it liberates HRM from intermediary roles, allowing them to focus on strategic planning in HR organizations and transforming HR practitioners from administrative paper handlers to strategic planners.
Keywords: 330; administrative expert; electronic HRM (E-HRM); HR practitioners; strategic partner